Pengembangan kemampuan matematis siswa berbasis 4C - Shofia, Rifatul Audia (Maliki Interdisciplinary Journal, 2024)
The ability to think mathematics is the ability to solve problems in mathematics where students are required to develop competence in thinking which is used as a basis in the teaching and learning process. In Indonesia, the ability to think mathematically can be said to be still low. To solve these problems, 4C-based learning is used. 4C-based learning itself is 21st century learning that prioritizes learning skills and innovation. Nowadays learning is about creativity, collaboration, communication, and critical thinking commonly called the 4C. 4C-based learning is important for students because they think, work together and share ideas with others. This is appropriate to overcome students' thinking skills with the application of the 4C.